Adolescent Sexual Abuse Victims’ Grief Experiences Through Kubler-Ross Theory - Hani, Alina Zulfa Marsya; Irawan, Andi Wahyu (International Journal of Applied Guidance and Counseling, 2026)
Sexual harassment is the behavior of asking for unwanted sexual activity, whether physical, verbal, or otherwise. This study aims to understand the experiences of victims of sexual harassment through Kubler-Ross's 5 stages of Grief, namely denial, anger, bargaining, depression, and acceptance, so that victims of sexual harassment can understand the stages of non-death grief, not feel alone, and not blame themselves. The method used is a qualitative case study approach. Data collection was carried out through interviews, observation, and documentation. Participants were 16-year-old female students who experienced sexual harassment. Data analysis techniques through 4 stages: data collection, data reduction, data presentation, and drawing conclusions. Data validity techniques were carried out by triangulation of source data, namely by combining the results of interviews, observations, and documentation, and strengthened by previous research. The results of the study showed that participants experienced 5 stages of grief, although not sequentially.